Auditing Water Management to Achieve Sustainable Development in Supply Chain - Hamdan, Dr. Khawla Hussein (International Journal of Supply Chain Management, 2018)
Abstract- The research aims at auditing water management to identify the extent to which water management contributes to the achievement of 2030 sustainable development in supply chain goal no.6. Statistical reports and time series were used to estimate percentages to some indicators. The research aims at utilizing indicators within SD (economic, social, environmental and institutional) dimensions to know how water management contributes to the achievement of SD. The researcher has concluded a set of conclusions the most important of which are the following: water reserves are not being maintained, efficient use of water has not been achieved due to high rates of water withdrawn from surface water, non-provision of safe drinking water and appropriate sanitation, inequality of water provision between country and urban population, low rate of wastewater treatment, most wastes of various activities are disposed of by being dumped in rivers untreated and high rate of morbidity resulting from water pollution. Despite the efforts exerted either by projects and plans or water related conventions, no effect has been seen on water management reality to achieve SD. Hence, water management has not achieved targets of goal 6 of 2030 development Agenda.